Understanding and Controlling the Irritable Bowel - El-Salhy, Magdy; Hatlebakk, Jan Gunnar; Hausken, Trygve (Springer International Publishing : Imprint: Springer, 2015)
This easy-to-read book gives sufferers of irritable bowel syndrome (IBS) strategies to improve both their symptoms and quality of life. Up-to-date information about IBS is provided and developments in the understanding and management of IBS from the last decade are discussed, by authors who are gastroenterologists with long experience of working with IBS patients. Each chapter begins with a summary containing the most important points, and includes a large number of illustrations. Thus, the reader can obtain a quick overview by simply reading the summary of each chapter and going through the illustrations; chapters of interest can be read in more detail when more time is available. Understanding and Controlling the Irritable Bowel helps patients suffering from this disorder to manage it and to prevent it from interfering with their everyday activities.